Travel Planning Ability in Right Brain-Damaged Patients: Two Case Reports - Bocchi, Alessia; Palmiero, Massimiliano; Boccia, Maddalena; Di Vita, Antonella; Guariglia, Cecilia; Piccardi, Laura (Frontiers in Human Neuroscience, 2020)
Planning ability is fundamental for goal-directed spatial navigation. Preliminary findings from patients and healthy individuals suggest that travel planning – namely, navigational planning – can be considered a distinct process from visuo-spatial planning ability. In order to shed light on this distinction, two right brain-damaged patients without hemineglect were compared with a control group on two tasks aimed at testing visuo-spatial planning (i.e., Tower of London-16; ToL-16) and travel planning (i.e., Minefield Task; MFT). The former requires planning the moves to reach the right configuration of three coloured beads on three pegs, whereas the latter was opportunely developed to assess travel planning in the navigational environment when obstacles are present. Specifically, the MFT requires participants to plan a route on a large carpet avoiding some hidden obstacles previously observed. Patient 1 showed lesions encompassing the temporo-parietal region and the insula; she performed poorer than the control group on the ToL-16 but showed no deficit on the MFT. Conversely, Patient 2 showed lesions mainly located in the occipito-parietal network of spatial navigation; she performed worse than the control group on the MFT but not on the ToL-16. In both cases performances satisfied the criteria for a classical dissociation, meeting criteria for a double dissociation. These results support the idea that travel planning is a distinct ability and that it is dissociated from visuo-spatial planning skill.